Solubility isotherms determination of the H3BO3 + CsCl + H2O system at T = (273.15, 298.15, 323.15, 348.15 and 363.15) K and thermodynamic modeling. (July 2022) - Zhuang, Ziyu; Li, Dongdong; Fan, Yanfei; Gao, Dandan; Zeng, Dewen
Highlights: Solubility isotherms of the H3 BO3  + CsCl + H2 O system are determined at various temperatures. A novel double salt 2H3 BO3 ∙3CsCl is found and its crystal structure has been solved. Solubilities of the H3 BO3  + CsCl + H2 O system are modeled and polythermal diagram is constructed. Standard thermodynamic quantities of 2H3 BO3 ∙3CsCl are derived from thermodynamic model. Abstract: The construction of a comprehensive thermodynamic model for boron-containing salt brine is important. However, the general lack of the solubility of H3 BO3  + salt + H2 O ternary systems makes it difficult to determine model parameters involving boron species. Here, we systematically determined the solubility isotherms of the H3 BO3  + CsCl + H2 O system at T = (273.15, 298.15, 323.15, 348.15 and 363.15) K. There are three solubility branches corresponding to H3 BO3(cr), CsCl(cr) and a novel adduct in the system. The determined composition of the adduct is 2H3 BO3 ·3CsCl. Moreover, the single crystal structure of 2H3 BO3 ·3CsCl is solved, suggesting that H3 BO3 molecules keep it native plane-triangle structure, but the O atoms coordinate to the Cs ion. We modeled these ternary solubility isotherms using the Pitzer-Simonson-Clegg (PSC) model implemented in the ISLEC program. With the help of the model, a complete polythermal phase diagram of the system was constructed for the temperature range from 250 K to 373.15 K. The determined standard thermodynamic quantities of 2H3 BO3 ·3CsCl(cr) from the model are Δ f G m Θ  =  − 3182.26 kJ∙mol −1, Δ f H m Θ  =  − 3496.19 kJ∙mol −1, S m Θ  = 485.85 J∙K −1 ∙mol −1, C p, m Θ  = 320 J∙K −1 ∙mol −1, respectively.